Effect of method of embedding in the learning phases of sprint sprint and skill upgrading in the high jump - Ali, Abed (Journal of Physical Education, 2010)
In order to advance in level of Physical Education College students especially they have activities various methods and measurements of teaching, therefore physical education teacher is must be having a good knowledge of teaching methods.The research importance is appear in application of inclusion style (to contain), it is one of the styles effective to learn through preparation in instructional curriculum for teaching the first stages in high jump skill, this stage is running approximation it is significant stage for skill, this stage is running approximation it is significant stage for skill on research persons, students are first stage in sport education college, they are learn these skill to once first, this curriculum "inclusion style" gives for students to control running steps number, distance of steps, length of steps, speed of steps, all those be suitable for student abilities also students are conditioned in this efficacious stage for performance improving.After the finish of curriculum application, it has been the tests gave excellence result to use "inclusion style" in compare with "instruction style" therefore this style must use to learn this skill and other skills for attaining high level of students.